Evolution of the EU broadband policy: Towards an integrated framework? - Orada Teppayayon; Erik Bohlin (International Telecommunications Society (ITS), 2011)
Since more than two decades, broadband has been recognized in the EU as having great benefits to economic and social development.This recognition is evident in the first EU policy document on the telecommunications market - the 1987 Green Paper - which assumed that harmonization and liberalization through competition mechanism could be used as the tools to bring all those benefits to the European citizens. Although the policy in the following years emphasized the competition mechanism, many additional instruments were developed and implemented in order to make broadband available to all European citizen. Some instruments can be seen in the form of Directives, and some instruments are shown in many policy strategies. All of them have a considerable contribution to the growth of broadband deployment in the EU. However, with globalization, the policy impetus for broadband has shifted toward a means to increase competitiveness of a nation or region.This changing emphasis due to globalization and competitiveness impacts the design of policy instruments. A question can be raised which instruments can serve a new concept of future broadband policy. Against this background, the paper will present an evolutionary concept of broadband policy in the EU by providing a model to integrate the related broadband policy instruments. A timeline of all instruments and initiatives being implemented will be explored. This evolution will be analyzed in order to see what kind of future model is applicable when broadband policy is based on a perspective of globalization and regional competitiveness. The analysis will address how well the existing instruments can serve a new concept of broadband policy and what the needs are for new policy instruments and working structures.
Keywords: 330; network society; post-industrial society; broadband policy; the EU; sector; agenda; strategic agenda